2016
DOI: 10.5966/sctm.2015-0116
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy With Adipose-Derived Mesenchymal Stem Cells and Ciprofloxacin Against Acute Urogenital Organ Damage in Rat Sepsis Syndrome Induced by Intrapelvic Injection of Cecal Bacteria

Abstract: Combined therapy with autologous adipose‐derived mesenchymal stem cells and ciprofloxacin was found to be superior to either therapy alone in improving the outcome in a rodent sepsis model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 28 publications
(78 reference statements)
4
36
0
Order By: Relevance
“…MSC therapy has reduced rodent mortality in SS [ 32 ], and both autologous and allogenic ADMSC have the capacity of immune privilege [ 16 , 29 , 31 33 ]. The present study showed that in animals with ARDS-SS, early administration of xenogeneic MSC reduces the mortality rate compared to no treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MSC therapy has reduced rodent mortality in SS [ 32 ], and both autologous and allogenic ADMSC have the capacity of immune privilege [ 16 , 29 , 31 33 ]. The present study showed that in animals with ARDS-SS, early administration of xenogeneic MSC reduces the mortality rate compared to no treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure and protocol for Western blot analysis were based on our recent reports [ 32 , 35 , 37 ]. Briefly, equal amounts (50 μg) of protein extracts were loaded and separated by SDS-PAGE using acrylamide gradients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve improved fat-graft survival, ADSC based-tissue engineering and regeneration are recently co-introduced in the surgical fields where autologous fat grafts alone have been in charge [3456]. Recent studies have also investigated whether stem cell therapy with ADSCs can be used for improving the outcome of patients in intensive care units, including the acute urogenital organ damage observed in sepsis [7] and toxic shock syndrome [8]. Several factors should be considered to achieve successful stem cell therapy [9].…”
Section: Introductionmentioning
confidence: 99%